2016
DOI: 10.1016/j.jtho.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Knowledge, Beliefs, and Distress Associated with Detection and Evaluation of Incidental Pulmonary Nodules for Cancer: Results from a Multicenter Survey

Abstract: Introduction Pulmonary nodules are detected in over a million Americans each year. Prior qualitative work suggests the detection of incidental pulmonary nodules can be burdensome for patients, but it is unknown whether these findings generalize to a broader sample of patients. We categorized patients’ knowledge, beliefs, and distress associated with detection and evaluation of a pulmonary nodule, and their impressions of clinician communication. Methods We administered a cross-sectional survey to adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 44 publications
(77 reference statements)
4
67
0
Order By: Relevance
“…Participants with indeterminate results reported increases in distress consistent with previous research . However, there was an apparent lack of concern about incidental findings (eg COPD) among some participants who were understandably pleased their scan showed no sign of lung cancer but in some cases regarded this an ‘all‐clear’ for their respiratory health.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Participants with indeterminate results reported increases in distress consistent with previous research . However, there was an apparent lack of concern about incidental findings (eg COPD) among some participants who were understandably pleased their scan showed no sign of lung cancer but in some cases regarded this an ‘all‐clear’ for their respiratory health.…”
Section: Discussionsupporting
confidence: 76%
“…Participants with indeterminate results reported increases in distress consistent with previous research. 6,8,22 However, there was an apparent lack of concern about incidental findings (eg COPD) among some participants who were understandably pleased their scan showed no sign of lung cancer but in some cases regarded this an 'all-clear' for their respiratory health. This suggests that incidental findings carry low risk of psychological distress which is reassuring, but also implies risk of over-reassurance akin to 'clear' screening results raised by a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the psychological impact of a pulmonary nodule diagnosis have found contrasting results. (18,19,24,35,36) Two studies in America found that individuals diagnosed with pulmonary nodules reported emotional distress (measured using the IES) shortly after diagnosis (time not specified)(35) and up to 2 or more years after diagnosis (19, 36).These findings differ from our study and those of the NELSON trial, with the latter showing an early (2 months after diagnosis)(18) and temporary clinically important increase in IES scores in individuals with nodules. (19) Additionally, the NELSON trial did not find that health-related quality of life (HRQoL) was affected by a pulmonary nodule diagnosis (19), which contrasts with a study in France.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Also, the psychological impact on patients is an aspect that needs more attention [21]. According to Freiman et al [22], 25% of patients experience clinically significant nodule-related distress, directly influencing patients' quality of life. The classifier needs optimisation, as this study suggests that 3% of the cancer patients might be missed.…”
Section: Implications For Practicementioning
confidence: 99%